Preliminary Design Pada Perancangan Merchandise Resmi Untuk Revenue Generated ITS Sebagai PTNBH - Ramadhani, Nugrahardi; Setyadi, Denny Indrayana; Alamin, Rabendra Yudistira; Prasetyo, Didit (Jurnal Bahasa Rupa, 2018)
The Revenue Generated ITS program as part of ITS Strategic Plan of PTNBH 2015-2019 provides a new challenge for ITS to develop business programs that departs from the intellectual result of all academic community. One of the opportunities that can be initiated is the development of official ITS merchandise products as a commercial product of ITS. ITS Merchandise product development efforts has been finding a variety of obstacles, ranging from inconsistencies between the products with each other, the quality of the existing product quality, up to the quality of the resulting product ideas. ITS Merchandise product development efforts are considered very urgent to be done immediately to see the high demand for ITS official merchandise products for various ITS activities. The method used in this research is the method of designing product design variants. Some stages of research include: (1) identification of design typology merchandise; (2) identification of consumers and product needs of ITS Merchandise; (3) Mapping merchandise product categories; (4) Development of product design merchandise variant; (5) Materials analysis and merchandise ITS Design Form; (6) Sampling of 1 prototype product; (7) Preparation of ITS Merchandise Product Design Guidelines. The approach used in variant product development in this research is âmorphological chartâ. The results to be achieved in this research is the identification of ITS Merchandise product line and its implementation, and A guide to merchandise product design development at production stage.